Optimization of Stope Structure Parameters Based on the Mined Orebody at the Meishan Iron Mine - Mingzhi Sun; Fengyu Ren; Hangxing Ding (Advances in Civil Engineering)
Based on the engineering background of the Meishan iron mine with sublevel caving (SLC) method, in this work, we adopted the method for identifying the shape of mined orebody (the original location in blasted slice), which analyzed and determined reasonable stope structure parameters. In the field test, the markers were arranged in the blasted slice, the mined orebody was measured by in situ tests, and reliable data were achieved. The shape of the mined orebody was obtained through this test when the width of drift was 6 m. The mined orebody’s shape was compared with the shape of the isolated extraction zone (IEZ), and the difference increased with increasing height. When the stope structural parameters were determined by the mined orebody, the larger the sublevel height was, the smaller the error was, which was compared with the method using ellipsoid arrangement theory to determine the stope structural parameters. Finally, the reasonable stope structure parameters were optimized. The sublevel height was 22 m, and the drift spacing was 20 m.